Ethanol Activation of Protein Kinase A Regulates GABAA Receptor Subunit Expression in the Cerebral Cortex and Contributes to Ethanol-Induced Hypnosis - Kumar, Sandeep; Ren, Qinglu; Beckley, Jonathan; O'Buckley, Todd; Gigante, Eduardo; Santerre, Jessica; Werner, David F.; Morrow, A Leslie (Frontiers in Neuroscience, 2012)
Protein kinases are implicated in neuronal cell functions such as modulation of ion channel function, trafficking, and synaptic excitability. Both protein kinase C (PKC) and A (PKA) are involved in regulation of γ-aminobutyric acid type A (GABAA) receptors through phosphorylation. However, the role of PKA in regulating GABAA receptors (GABAA-R) following acute ethanol exposure is not known. The present study investigated the role of PKA in the effects of ethanol on GABAA-R α1 subunit expression in rat cerebral cortical P2 synaptosomal fractions. Additionally, GABA-related behaviors were examined. Rats were administered ethanol (2.0–3.5 g/kg) or saline and PKC, PKA, and GABAA-R α1 subunit levels were measured by western blot analysis. Ethanol (3.5 g/kg) transiently increased GABAA-R α1 subunit expression and PKA RIIβ subunit expression at similar time points whereas PKA RIIα was increased at later time points. In contrast, PKC isoform expression remained unchanged. Notably, lower ethanol doses (2.0 g/kg) had no effect on GABAA-R α1 subunit levels, although PKA type II regulatory subunits RIIα and RIIβ were increased at 10 and 60 min when PKC isozymes are also known to be elevated. To determine if PKA activation was responsible for the ethanol-induced elevation of GABAA-R α1 subunits, the PKA antagonist H89 was administered to rats prior to ethanol exposure. H89 administration prevented ethanol-induced increases in GABAA-R α1 subunit expression. Moreover, increasing PKA activity intracerebroventricularly with Sp-cAMP prior to a hypnotic dose of ethanol increased ethanol-induced loss of righting reflex (LORR) duration. This effect appears to be mediated in part by GABAA-R as increasing PKA activity also increased the duration of muscimol-induced LORR. Overall, these data suggest that PKA mediates ethanol-induced GABAA-R expression and contributes to behavioral effects of ethanol involving GABAA-R.